Teacher and Students' Responses of Using Telegram as a Media in Learning English Listening Skill - -, Uswatun Khasana; Saputri, Tiyas (Universitas Nahdatul Ulama Surabaya, 2021)
This study is to investigate teacher’s and students’ responses of using Telegram in learning English listening skills. The focus of this study is the teacher’s and students’ responses about using Telegram as a media in learning English listening skills. This study used qualitative research methods by describing the results of teacher’ and students’ responses obtained from questionnaires distributed to the teacher and the students. The findings of this study showed that teacher’s and students’ responses are positive regarding the use of Telegram as a media for learning English listening skill.